Strategic Information Systems Planning In The Banking Sector—a Path Analytic Model Study In The Indian Context - A. M. Rawani, A. M. Rawani; M. P. Gupta, M. P. Gupta (Asian Academy of Management (AAM), 2002)
This paper presents a path analytic model showing the cause and effect relationships among various Information Systems (IS) planning variables for the banking sector in India. In recent years, there has been an increased awareness among banks of the potential of Information Technology (IT) and the use of information systems. Strategic information system planning (SISP) becomes an important issue in the use of IS strategically. In India, banks have now started realizing the importance of SISP. In this study, 11 IS planning variables for the banking sector in India are examined and the influence of one over the other is investigated using path analysis. Data for the study are collected from 52 banks operating in India. The results of the study indicate that top management involvement in IS planning greatly influences the whole planning exercise. Moreover, top management involvement is higher when they foresee greater future impact of IS. The study also highlights the need and importance of user training in the banking sector. Change in the focus and orientation of user-training will make the users competent to conceive with innovative IS applications.